1970
DOI: 10.1039/tf9706602420
|View full text |Cite
|
Sign up to set email alerts
|

E. s. r. and ionic association. Formation of ion pairs and triple ions of 9,10-anthrasemiquinone

Abstract: Electron spin resonance spectra of 9,lO-anthrasemiquinone as the free ion, ion-pair and triple ion (counter ion, Na+) in tetrahydrofuran, and as the triple ion in 2-methyltetrahydrofuran are presented and discussed in terms of the structures of the ionic associates. The ion-pair is " locked-in " to an asymmetric configuration at -65"C, but at 20°C intramolecular transfer of the cation between the oxygens of the anion is observed. The triple ion is symmetrical, one sodium associating with each oxygen, and occup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1970
1970
2005
2005

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It has been established from the above voltammetry that, in the presence of lithium cations, the electrogenerated anthraquinone radical anion becomes ion paired and that some of the complexed radical anions are removed from solution at the electrode surface via precipitation, which suggests that the total number of radical anions that are uncomplexed and essentially “free” in solution is likely to be reduced. Since the radical anion is known to demonstrate a hyperfine ESR spectrum, ,, it was envisaged that the method of simultaneous electrochemical ESR could be used to provide more information about the ion association equilibrium, and so experiments were carried out using a tubular flow cell for use in generating the radical anions in situ.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been established from the above voltammetry that, in the presence of lithium cations, the electrogenerated anthraquinone radical anion becomes ion paired and that some of the complexed radical anions are removed from solution at the electrode surface via precipitation, which suggests that the total number of radical anions that are uncomplexed and essentially “free” in solution is likely to be reduced. Since the radical anion is known to demonstrate a hyperfine ESR spectrum, ,, it was envisaged that the method of simultaneous electrochemical ESR could be used to provide more information about the ion association equilibrium, and so experiments were carried out using a tubular flow cell for use in generating the radical anions in situ.…”
Section: Resultsmentioning
confidence: 99%
“…When paramagnetic anions are generated, electron spin resonance (ESR) provides an elegant method with which to study ion pairing effects in the solution phase, since the observed spectra are often dramatically altered by such ionic associations. , Metal cations possessing magnetic nuclei often couple with the radical anions such that additional hyperfine splitting arises, and slow cation exchange between equivalent sites on the anion, such as the oxygen atoms in many semiquinones, can result in a line width alternation effect . Ion pairing has been studied using ESR for a number of semiquinones in various solvent systems, in which the radical anions were commonly generated using alkali metal reduction, but alternatively by flash photolysis methods …”
Section: Introductionmentioning
confidence: 99%
“…and Q ; in photolyzed solutions of quinones in alcoholic solvents have been demonstrated by electron spin resonance (E.S.R.) spectroscopy [2,3]; however, the only kinetic studies which have been carried out on these systems have utilized optical absorption techniques. As a part of a continuing interest in the kinetics of quinone reactions in photosynthetic systems and corresponding model systems, we have undertaken an investigation of the radicals involved in the photochemical reaction of chloranil with methanol and ethanol.…”
Section: * Q T + H +mentioning
confidence: 99%